Cyfrowy świat w podręczniku dla klasy pierwszej szkoły podstawowej – analiza treści - Beata Adrjan; Alina Kalinowska (Problemy Wczesnej Edukacji)
The digital world is becoming accessible to ever younger children, who are increasingly looking for and building their presence in it. The school seems to be a place that should respond to these trends by incorporating digitality into its educational proposals. Research into the content of textbooks for the first year of primary school shows infantile character and inadequacy in time and cognition of content related to the digital world. First-grade students are unlikely to encounter (in the currently offered school’s curriculum) a reflection on the dangers it poses or proposals to use digital skills. The contents of the textbooks constitute a world existing alongside the digital natives.